The specifics in the work of social workers when rendering social services at the person's home - Raudeliunaite Rita (SHS Web of Conferences, 2019)
The objective of the study is to highlight the specifics of the work of a social worker when rendering social services at the person's home on the basis of the experience of social workers. Qualitative research strategy was used, including semi-structured interview. The study revealed a wide spectrum of the activities of the social worker when organising the provision of social services at home: the identification and assessment of the need for a service, the planning, provision, coordination and assessment of the assistance or care at the person's home, the involvement of the service recipient in decision-making, the involvement of close relatives of the service recipient, teamwork, cooperation with other institutions, and improvement of skills of the employees. The study revealed the benefit of social services at the person's home to the recipients of the services: living at their homes, they do not feel so lonely, they feel safe, needful, capable of benefiting from the needed assistance. Difficulties, which arise when cooperating with the recipients of social services at home, are the following: people provide false information when identifying the need for a service, mental disorders of the service recipient, dissatisfaction with the rotation of the visiting care workers, complaints regarding the lack of communication. Organisational limitations of bodies providing services are linked to formalism, shortage of the staff, time restrictions for services, lack of transport, unavailability of services due to the limited financial resources of service recipients.